Atividade eletromiográfica e cocontração dos músculos do tronco durante exercícios realizados com haste oscilatória: uma análise do efeito de diferentes posturas - Martins, Luis Renato Garcia Martinez; Marques, Nise Ribeiro; Ruzene, Juliana Rodrigues Soares; Morita, Ângela Kazue; Navega, Marcelo Tavella (Universidade de São Paulo, 2015)
This study aimed at analyzing the electromyographic activity (EMG) and cocontraction of torso muscles during exercises with a flexi bar, in two different postures (neutral pelvis and posterior pelvic tilt). 20 young women with no lower back pain took part in the study (ages between 18 and 28 years) and they were recruited from a university population. In order to collect the data, an exercise was performed with a flexi bar being held with both hands. It was perpendicular to the ground and it was oscillating in the sagittal plane. That exercise was conducted in two different pelvis postures (neutral and posterior tilted). The EMG signals were collected bilaterally on the following muscles: internal oblique (IO), rectus abdominals (RA), iliocostalis lumborum (IL) and multifidus (MU). The analysis of variance (ANOVA) of repeated measurements was found to display an interaction between muscles and postures (F=5.18; p=0.003). The activation of IL muscle in the neutral posture was 7.93% higher than in the posteriorly tilted posture (p=0.005), and the activation of IO muscle was 13.62% higher in the posteriorly tilted posture than during the exercise in the neutral posture (p=0.002). According to our results, the performance of the exercise with a posteriorly tilted pelvis increased the activation of IO muscle, whereas IL muscle was found to have a higher activation when the exercise was performed in a neutral posture. Future studies need to be conducted in order to understand the neuromuscular adaptations that are generated by exercises with flexi bars, and their relevance to the prevention and treatment of nonspecific lower back pain.

Este estudio tuvo por objetivo analizar la actividad electromiográfica (EMG) y la co-contracción de los músculos del tronco durante el ejercicio con barra oscilante en dos posturas distintas, la pelvis neutral y la en retroversión. Participaron veinte mujeres entre los 18 hasta los 28 años de edad, sin dolor lumbar, reclutadas en una universidad. La recolección de datos se realizó por un ejercicio con barra oscilante, que colocada verticalmente al suelo, podría ser agarrada por ambas manos de las participantes y, así, oscilar en el plan sagital. Las señales EMG se recogieron de forma bilateral en los músculos oblicuo interno (OI), recto abdominal (RA), iliocostal lumbar (IL) y multifidus (MU). El análisis de la varianza (ANOVA) de las medidas repetidas mostró interacción entre músculos y posturas (F=5,18, p=0,003), siendo que la activación del músculo IL en la postura neutral fue un 7,93% mayor que en la postura en retroversión (p=0,055) y la activación del músculo OI fue un 13,62% mayor en la postura en retroversión que durante el ejercicio en la postural neutral (p=0,002). Con respecto a los resultados, el ejercicio realizado con la postura en retroversión de la pelvis aumentó la activación del músculo OI, mientras que el realizado con la postura neutral aumentó la activación del músculo IL. Es necesario que se hagan futuros estudios para comprender mejor las adaptaciones neuromusculares generadas por el entrenamiento con ejercicios con barra oscilante y su importancia para la prevención y el tratamiento del dolor lumbar inespecífico.

O objetivo deste estudo foi analisar a atividade eletromiográfica (EMG) e cocontração dos músculos do tronco durante a realização de exercícios com haste oscilatória em duas diferentes posturas (pelve neutra e pelve em retroversão).Participaram do estudo 20 mulheres jovens (idades entre 18 e 28 anos),sem dor lombar, recrutadas em uma população universitária. Para a coleta de dados foi realizado um exercício com haste oscilatória posicionada verticalmente ao solo, sendo segurada com ambas as mãos e oscilando no plano sagital. Este exercício foi realizado em duas diferentes posturas da pelve (neutra e retrovertida). Os sinais EMG foram coletados bilateralmente, sobre os músculos: oblíquo interno (OI), reto abdominal (RA), iliocostal lombar (IL) e multífidos (MU). A análise de variância (ANOVA) de medidas repetidas demonstrou interação entre músculos e posturas (F=5,18; p=0,003), sendo que a ativação do músculo IL na postura neutra foi 7,93% maior do que a postura retrovertida (p=0,055), e a ativação do músculo OI foi 13,62% maior na postura retrovertida do que durante o exercício em postura neutra (p=0,002). De acordo com os nossos resultados, a realização do exercício em postura com retroversão da pelve aumentou a ativação do músculo OI, enquanto o músculo IL apresentou maior ativação durante a realização do exercício em postura neutra. Futuros estudos são necessários para o entendimento das adaptações neuromusculares geradas pelo treino com exercícios com haste oscilatória e sua relevância para a prevenção e tratamento da dor lombar inespecífica.
Electromyographic activity and cocontraction of trunk muscles during exercises performed with an oscillatory pole: an analysis of the effect of different postures
Actividad electromiográfica y co-contracción de los músculos del tronco durante ejercicios con barra oscilante: análisis del efecto de diferentes posturas
Keywords: Electromyography; Physical Therapy Modality; Applied Kinesiology; Lower Back Pain; Eletromiografia; Modalidade de Fisioterapia; Cinesiologia Aplicada; Dor Lombar